2017
DOI: 10.1177/0954407017698304
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into a stepped-piston engine solution for automotive range-extender vehicles and hybrid electric vehicles to meet future green transportation objectives

Abstract: Securing the objectives for future high efficiency low CO2 vehicles is a key target for automotive manufacturers. This paper considers a high durability two-stroke cycle engine in terms of performance and computational modelling of emission characteristics for automotive range-extender or hybrid electric vehicle power plant application. The engine uses novel segregated pump charging via the application of stepped pistons and the study compares the engine characteristics with a comparable four stroke cycle engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The very low NO x emission of two-stroke engines as discussed by Blundell et al 37 and Turner et al 22 has been observed with stepped piston engines, 14,23 but the implementation of variable compression ratio (VCR) technology as discussed by Turner et al 22 could further reduce NO x emission and offer even greater CO 2 reductions. HEVs and RE-EVs already readily demonstrate fuel efficiency improvements and therefore reduced CO 2 emissions but application of VCR gives further potential reduction beyond the immediately apparent benefits while also addressing the range anxiety issues of fully electric vehicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The very low NO x emission of two-stroke engines as discussed by Blundell et al 37 and Turner et al 22 has been observed with stepped piston engines, 14,23 but the implementation of variable compression ratio (VCR) technology as discussed by Turner et al 22 could further reduce NO x emission and offer even greater CO 2 reductions. HEVs and RE-EVs already readily demonstrate fuel efficiency improvements and therefore reduced CO 2 emissions but application of VCR gives further potential reduction beyond the immediately apparent benefits while also addressing the range anxiety issues of fully electric vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has been performed in this area with balance shaft application with four-stroke inline three-cylinder units as the subject engine [6][7][8][9][10]. Two-stroke cycle engines for range extenders or hybrid drive train have been researched by Stan and Personnaz [11], Mattarelli et al [12], Borgi et al [13] and Hooper [14] [15]. Some researchers have considered the in-line three-cylinder twostroke cycle engine as a suitable candidate as demonstrated by the work of Duret et al [16], Schlunke [17], Cantore and Mattarelli [18], Mattarelli [19] and Mattarelli and Rinaldini [20], but none of these examples applied a balance shaft.…”
Section: Introductionmentioning
confidence: 99%
“…Other technologies which would be interesting to study in this context might be the stepped-piston concept, which could replace an external supercharger while still permitting turbocharging to be applied. This has been investigated extensively by Hooper [50,51] and also Lee [52] in a compounded engine, as well as being a feature (in inverted form) of the engine of Witzky et al [48].…”
Section: Comparison Of the Different Systemsmentioning
confidence: 99%
“…This paper considers such a method of LFG combustion using stepped piston engine technology as discussed by Hooper et al, 16 Stone, 23 Hooper et al, 24 and Hooper. [25][26][27][28] Comparisons are drawn between a twin-cylinder stepped piston engine and an equivalent four-stroke twin-cylinder engine.…”
Section: Introductionmentioning
confidence: 99%